Determination of Outdoor Relative Humidity and Design Temperatures for Different Climatic Zones in Libya - Bodalal, Awad Saad; Masheiti, Salah Ali; Moftah, Almahdi Othman; Alkezza, Ayman Khalifah (Journal of engineering sciences and information technology, 2022)
The importance of choosing external climatic parameters such as temperature and relative humidity, which naturally determine the energy consumption of such variables, is of paramount importance, especially if the measurement difference between indoor and outdoor conditions is extreme. Therefore, this study attempts to choose a more accurate design temperature and relative humidity for several Libyan cities based on climatic data over 30 years (1990–2020). By using the data of fifteen different meteorological observation stations, distributed over several climatic regions (the Mediterranean coast in the north and the desert in the south) in this study, By calculating the monthly average temperature and relative humidity over the mentioned years, hence, a code was constructed by Matlab capable of calculating the monthly average as well as choosing the design temperatures through data analysis, statistically based on the methodology and provisions set by ASHRAE for several Libyan cities for the first time (13 cities to be exact) and thus filling a large knowledge gap in the literature, especially calculations of energy consumed in buildings, as well as It was noted that the meteorological data that were analyzed during only two years in a previous study yielded results with a level of accuracy comparable to that of thirty years. Accordingly, it is therefore concluded that the data obtained over two years represents the minimum for any similar future endeavors.